Tracking the Traces of God in Science: Islamic Tafsir on Science - Mehdi Golshani; Reviewed by: Syamsul Kurniawan (Graduate Program of Pontianak Institute of Islamic Studies, 2015)
To Muslims, the Qur’an should serve as the model of thinking. It is a model which should become the paradigm. The advancement of science based on the paradigm of the Qur’an will obviously enrich science. This paradigm will subsequently trigger the emergence of alternative science. We understand that normative premises of the Qur’an can be formulated into empirical and rational theories. The transcendental structure of the Qur’an is an idea which is normative and philosophical in nature, and it can be formulated into a theoretical paradigm, and provide a framework for the development of empirical and rational science, based on the pragmatic needs of humans as the vicegerent on earth. Kuntowijoyo (2006) argued that the development of theories of Islamic science is intended for the welfare of the Muslims.